Inside Front Cover: Volume 2 Issue 4. (22nd December 2021) - Zhao, Yue; Liu, Liyao; Zhang, Fengjiao; Di, Chong‐an; Zhu, Daoben
Abstract : Inside front cover image : Organic thermoelectric (OTE) materials have been considered to be promising candidates for large area and low‐cost smart electronics owing to their intrinsic energy‐conversion property, as well as the tailorable molecular structure, intrinsic flexibility, and prominent solution processability. In this review, the authors summarized the fundamentals and recent developments of OTE materials and devices for flexible generators, photothermoelectric detectors, self‐powered sensors, and ultra‐thin cooling elements. Moreover, they figured out the basic requirements of OTE materials in the thermoelectric performance, mechanical properties and bionic functions, towards the wearable electronics and fascinating applications. With respect, the authors proposed the challenge and perspective of future investigation of OTE materials and devices enabled Internet of Things. (DOI: https://doi.org/10.1002/smm2.1034 )